DIFFERENCES OF CONVERSATIONAL FEATURES. POLITENESS AND HESISTATION. ("Conference on Universal Science Research 2023", 2023)
Children are taught to communicate from a young age, first in the family, and then in educational institutions. One of the ways to teach communication is the formation of communication skills in the form of training. In kindergarten, the teacher teaches the child to communicate by conducting various activities. First, basic manners, how to talk to adults, how to say hello, how to express gratitude are included. During school age and later, a person is taught to communicate through socio-psychological training. This article provides information on Differences of conversational features, Politeness and hesitation.